Endovascular treatment for dural arteriovenous fistulas in the petroclival region - Hou, Kun (Int J Med Sci, 2020)
Petroclival region dural arteriovenous fistulas (DAVFs) are rare and difficult lesions to manage. They often have very complex anatomical structures and can be further divided into the superior petrosal sinus, petrous apex, inferior petrosal sinus, upper clival, and upper clival epidural-osseous DAVFs. Most petroclival region DAVFs should be treated due to their high Cognard grades. Currently, endovascular treatment (EVT) has become the first-line therapeutic option for petroclival region DAVFs. But not all the petroclival region DAVFs could be cured with EVT. When the arterial feeders are large or the DAVF is adjacent to the venous sinus, the success rate may be higher. In petroclival region DAVFs, if EVT can be performed successfully, satisfactory outcome can be anticipated. However, there are some inadvertent complications, which include cranial nerve palsy, subsequent sinus thrombosis, and migration embolization of the internal carotid artery and vertebral artery. Currently, a review of the EVT of petroclival region DAVFs is lacking. In this article, we performed a review of the relevant literature on this issue. In addition, some illustrative cases would be provided to elaborate these specific entities.